Inclusive growth: What future for the European social model? - Günther Schmid (Institute for the Study of Labor (IZA), 2014)
This essay starts, after a short introduction on the importance and dimensions of "inclusive growth", with a brief empirical sketch on to what extent Europe has already succeeded with respect to this ambitious goal. The result is quite sobering and gives rise to the question: why is it so? The main part of this paper is devoted to answering this question by presenting a model based on the trade-off between comparable productive capacity (CPC) and flexibility. After the introduction of the monetary union, this trade-off sharpened for many EU member states whose CPC now falls below the fair level playing field. To compensate for the lack of comparable productive capacities, flexibility measures would be necessary (e.g. downward wage flexibility, regional mobility and cuts in social expenditures) to an extent which is unrealistic or would erode social cohesion and democracy. As alternative, the possible future role of the European Social Model could consist of the implementation of four strategies: First, investive social transfers, in particular by establishing a European Fund for Employment and Income Security (EIS) to strengthen the inclusive function and stabilisation impact of national unemployment insurance systems; second, protected flexibility, in particular the promotion of an internal functional flexibility through work sharing; third, investing in people, in particular by strengthening dual learning systems and by inducing mobility chains (making transitions pay); and fourth, efficient labour market regulation for better utilising existing capacities and restraining inefficient forms of flexibility. Examples for each strategy are presented to illustrate and stimulate the debate.
Keywords: E24; I31; J65; J83; O43; P16; 330; Europe; social policy; labour market policy; growth; inclusion; unemployment insurance